Generation and characterization of monoclonal antibodies specific to Coenzyme A - Malanchuk, O.M.; Panasyuk, G.G.; Serbyn, N.M.; Gout, I.T.; Filonenko, V.V. (Вiopolymers and Cell, 2015)
Aim. Generation of monoclonal antibodies specific to Coenzyme A. Methods. Hybridoma technique. KLH carrier protein conjugated with CoA was used for immunization. Screening of positive clones was performed with BSA conjugated to CoA. Results. Monoclonal antibody that specifically recognizes CoA and CoA derivatives, but not its precursors ATP and cysteine has been generated. Conclusion. In this study, we describe for the first time the production and characterization of monoclonal antibodies against CoA. The monoclonal antibody 1F10 was shown to recognize specifically CoA in Western blotting, ELISA and immunoprecipitation. These properties make this antiboby a particularly valuable reagent for elucidating CoA function in health and disease. Ціль. Отримати та охарактеризувати моноклональні антитіла, специфічні до КоА. Методи. Гібридомна технологія. Для імунізації було використано КоА, кон’югований з білком-носієм KLH. Скринінг позитивних клонів проводили з використанням БСА, кон’югованого з КоА. Результати. Отримано моноклональні антитіла, що специфічно розпізнають КоА та КоА-похідні та не розпізнають його попередників – АТФ та цистеїну. Висновки. Вперше описано створення та характеристику моноклональних антитіл проти КоА. Моноклональні антитіла 1F10 специфічно розпізнають КоА в Вестерн блотингу, ІФА та імунопреципітації. Такі властивості антитіл вказують на перспективність використання для аналізу функцій КоА в нормі та за патологій. Цель. Получить и охарактеризовать моноклональные антитела, специфичные к КоА. Методы. Гибридомная технология. Для иммунизации был использован КоА, конъюгированный с белком-носителем KLH. Скрининг положительных клонов проводили с использованием БСА, конъюгиванного с КоА. Результаты. Получено моноклональные антитела, которые специфично распознают КоА и КоА-производные и не распознают его предшественников – АТФ и цистеина. Выводы. Впервые описано получение моноклональных антител к КоА. Показано, что моноклональные антитела 1F10 специфически распознают КоА в вестерн плоте, ИФА и иммунопреципитации. Такие свойства антител указывают на возможность их использования для анализа функций КоА в норме и при патологиях.